Falls and Recurrent Falls among Adults in A Multi-ethnic Asian Population: The Singapore Epidemiology of Eye Diseases Study /692/700/478/174 /692/308/174 /692/499 /141 article - Dai, W (2020)
10.1038/s41598-018-25894-8